Enhancement of the ionoacoustic effect through ultrasound and photoacoustic contrast agents - Lascaud, Julie; Dash, Pratik; Würl, Matthias; Wieser, Hans-Peter; Wollant, Benjamin; Kalunga, Ronaldo; Assmann, Walter; Clevert, Dirk-André; Ferrari, Alfredo; Sala, Paola; Savoia, Alessandro Stuart; Parodi, Katia (Scientific reports, 2021)
The characteristic depth dose deposition of ion beams, with a maximum at the end of their range (Bragg peak) allows for local treatment delivery, resulting in better sparing of the adjacent healthy tissues compared to other forms of external beam radiotherapy treatments. However, the optimal clinical exploitation of the favorable ion beam ballistic is hampered by uncertainties in the in vivo Bragg peak position. Ionoacoustics is based on the detection of thermoacoustic pressure waves induced by a properly pulsed ion beam (e.g., produced by modern compact accelerators) to image the irradiated volume. Co-registration between ionoacoustics and ultrasound imaging offers a promising opportunity to monitor the ion beam and patient anatomy during the treatment. Nevertheless, the detection of the ionoacoustic waves is challenging due to very low pressure amplitudes and frequencies (mPa/kHz) observed in clinical applications. We investigate contrast agents to enhance the acoustic emission. Ultrasound microbubbles are used to increase the ionoacoustic frequency around the microbubble resonance frequency. Moreover, India ink is investigated as a possible mean to enhance the signal amplitude by taking advantage of additional optical photon absorption along the ion beam and subsequent photoacoustic effect. We report amplitude increase of up to 200% of the ionoacoustic signal emission in the MHz frequency range by combining microbubbles and India ink contrast agents.